Accounting reading in foreign operations and translation of financial statements - سلمان عامر محمد; عبد الله بشرى نجم; محمد صفاء (Journal of Economics and Administrative Sciences, 2009)
Recent decades have witnessed tremendous economic development that has led to the spread of international companies (multinational companies) and its activity has expanded to cover many countries of the world, with intense competition among countries to attract more international investments, which has led to the emergence of some controversial accounting issues in many Relevant areas, including accounting for transactions in foreign currencies, translation of financial statements for companies and foreign branches, as this issue is an important and sensitive topic because many of its aspects are controversial and not yet resolved, especially with regard to the variation in standards and Relevant accounting practices from one country to another, which attracts researchers to fool about the reasons for this and try to reach common points and reduce the gap between the options and theoretical and practical solutions available and in line with the environmental changes surrounding the companies concerned, and this research problem starts from a defect in the intellectual and conceptual reading of a topic Accounting for operations in foreign currencies and translating the financial statements of foreign branches and companies at the local level, which has led to the adoption of accounting standards, rules, and practices that are not sufficient or appropriate to address the issue, objective treatment consistent with the Emerging environmental changes that Iraqi companies operate under. The research dealt with the presentation and discussion of the topic in two axes, the first dealt with a conceptual approach to the operations that are done in foreign currencies and the translation of the financial statements of foreign branches and companies, while the second dealt with an analysis of the mentioned operations and translation of the financial statements of the branches and companies. Appropriate in this area.